2023
DOI: 10.1111/jdi.14015
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive protection of incretin‐based therapies in patients with type 2 diabetes mellitus: A systematic review and meta‐analysis based on clinical studies

Abstract: Aims/introduction Cognitive dysfunction, including mild cognitive impairment and dementia, is increasingly recognized as an important complication of type 2 diabetes mellitus. The aims of the preset study was to investigate the cognitive protection of incretin‐based therapies, including glucagon‐like peptide‐1 receptor agonists and dipeptidyl peptidase‐4 inhibitors, in patients with type 2 diabetes mellitus. Materials and Methods PubMed, EMBASE, Cochrane library, Web of Science and PsycINFO were searched from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Some glucose-lowering drugs have been shown to improve cognitive function in patients. Recent studies have found that glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and DPP-IV inhibitors are effective in ameliorating cognitive impairment in diabetic patients [23]. GLP-1 acts as a physiological modulator of the central nervous system and enhances learning and memory function by restoring insulin signaling [24].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Some glucose-lowering drugs have been shown to improve cognitive function in patients. Recent studies have found that glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and DPP-IV inhibitors are effective in ameliorating cognitive impairment in diabetic patients [23]. GLP-1 acts as a physiological modulator of the central nervous system and enhances learning and memory function by restoring insulin signaling [24].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Incretin-based treatments, which are widely used glucose-lowering drugs, have recently shown promise in improving cognitive functions among individuals with type-2 diabetes, positioning themselves as potential therapeutic agents for major CI [ 4 , 5 ]. Notably, a recent meta-analysis of cohort studies revealed that dipeptidyl peptidase-4 inhibitors (DPP-4i) can significantly improve cognitive functions in patients with type-2 diabetes compared to other classes of glucose-lowering agents (i.e., sulfonylurea and metformin) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incretin-based treatments, which are widely used glucose-lowering drugs, have recently shown promise in improving cognitive functions among individuals with type-2 diabetes, positioning themselves as potential therapeutic agents for major CI [ 4 , 5 ]. Notably, a recent meta-analysis of cohort studies revealed that dipeptidyl peptidase-4 inhibitors (DPP-4i) can significantly improve cognitive functions in patients with type-2 diabetes compared to other classes of glucose-lowering agents (i.e., sulfonylurea and metformin) [ 4 ]. In addition, glucagon-like peptide-1 analogues (GLP-1a) have garnered increased attention as pharmacological treatments capable of improving cognitive functions, supported by positive results from preclinical studies and some observational research [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%